Effects of E-recruitment and internet on recruitment process: An Empirical study on Multinational companies of Bangladesh (International Journal of Scientific Research and Management (IJSRM), 2018)
Recruitment is a function of human resource management by which an organization can attract the potential candidates and select the most appropriate employees for the organization. Now-a-days the people are extensively adaptive to the technology and that’s why e-recruitment has become a popular practice followed by the organization for hiring employees. This is an exploratory research with the aim of identifying how e-recruitment and internet is influencing the overall recruitment process of an organization in context of Multinational companies of Bangladesh. In this study, multinational organizations of Bangladesh have been taken as population according to their participation in e-recruitment activities. The sample was drawn from the renowned companies and data were collected from various levels of respondents in context of the job seekers. Statistical analysis has been used to prove that there is a significant statistical analysis of how e-recruitment is practiced and the relationship between e-recruitment and overall recruitment process. It also concluded that there is a moderate relationship between these two variables and the job seekers feel convenient to search potential jobs for their prosperous career. So it is recommended that the organization should continue to use e-recruitment and online sources for hiring candidates so that they can match with the global business world.